Effect of preparation design on fracture resistance of molars restored with occlusal veneers of different CAD-CAM materials: an in vitro study - Ahmed Ismail Taha; Mona Elshirbini Hafez (BMC, 2024)
Abstract Background Occlusal veneer had been evaluated for mechanical properties using lithium disillicate. However, studies evaluating the mechanical properties of occlusal veneer with different preparation designs and ceramic materials are lacking. So, this in vitro study aimed to evaluate the fracture resistance of occlusal veneers with two designs fabricated from two different ceramic materials. Material and methods Fourty mandibular third molars were distributed to 2 groups (n = 20) according to preparation design: group (O) anatomical occlusal reduction and group (OA) anatomical occlusal and 1 mm axial reduction. Each group was additionally subdivided into two subgroups (n = 10) according to ceramic materials; in subgroup X, lithium disilicate (e.max CAD, Ivoclar AG, Schaan, Liechtenstein) was used, and in subgroup S, zirconia-reinforced lithium silicate (ZLS) (Vita Suprinity, VitaZahnfabrik, Bad Säckingen, Germany) was used. All specimens were cemented with a light-cure resin cement (Choice 2, Bisco, Schaumburg, USA). 5000 thermocycles were applied to all specimens with both temperatures of 5 °C and 55 °C in two water baths; the dwell time was 30s at each bath, and the transfer time was 10s. Then all specimens were subjected to a fatigue simulation under dynamic loading of 200 N for 250,000 cycles. A universal testing machine (5500R/1123, Instron, Norwood, USA) was used to evaluate the fracture strength with a crosshead speed of 1 mm/min. All data were analyzed statistically by using a two-way ANOVA, and for some violations of assumptions, these results were compared with those obtained by the nonparametric test (Scheirer Ray Hare) (α = 0.05). Results A statistically significantly higher fracture resistance in the 'OA' (3389 N) compared to the 'O' (2787 N) group regardless of the ceramic material (P < .001) and a statistically significantly higher fracture resistance in the 'X' (3295 N) compared to the 'S' (2881 N) regardless of the preparation design (P = .015). Conclusions For occlusal veneers, all preparation designs and materials (such as Vita Suprinity and e.max CAD) had clinically acceptable fracture resistance values that were greater than the maximal biting forces. On the other hand, the e.max CAD with occlusal veneer, including axial reduction design, demonstrated the maximum fracture resistance value. Finally, no relationship between fracture strength and mode of failure was found.